Improving management as a way to increase labour productivity - A. O. Ivanov (Управление)
The article gives an overview, performs analysis and classification of successful managerial practices applied at Russian industrial enterprises in the framework of the national project “Labour productivity and employment support”. The paper emphasizes the main factors of labour productivity growth as follows: investment policy, growth of human capital, and efficient use of managerial capital of enterprise. In order to determine the need of enterprises to increase labour productivity, the author proposes four universal criteria that signal the existing inefficiency even before the loss of competitiveness: 1) the dynamics of labour productivity in the company is not positive during a given period; 2) the company is behind competitors by labour productivity indicator; 3) the company is behind competitors by labour productivity growth rates indicator for a certain period; 4) unit production costs rise. These criteria allow you to take into account the situation both within the enterprise and in comparison with other enterprises. Each criteria can be considered separately or in combination with the others, applied to enterprises of different industries, specialization, and scale. Criteria indicate the direction of development in which the company is experiencing difficulties at the moment, or may experience them in the future.